Gene variations and sweet taste sensitivity in Zambian adults with and without type 2 diabetes mellitus - Tuku Mwakyoma; Catherine Anna-Marie Graham; Benson M. Hamooya; Lweendo Muchaili; Memory Ngosa; Joreen P. Povia; Leta Pilic; Sepiso K. Masenga (PLoS ONE, 2025)
Background Sweet taste perception and preference play crucial roles in dietary habits and health outcomes. Understanding the genetic basis of taste thresholds and preferences can provide insights into individual differences in dietary behavior and susceptibility to metabolic disorders such as type 2 diabetes mellitus (T2DM). In Zambia, there is paucity of data concerning taste perception and preference in relation to genetics among diabetic and non-diabetic individuals. This study aimed to determine the relationship between the genotype and sweet taste thresholds, among individuals with and without T2DM in Zambia. Methods A cross-sectional study was conducted among 89 adults at Livingstone University Teaching Hospital (42 non-diabetic and 47 diabetics). Saliva samples were used to determine the TRPV1 rs4790522, and TAS1R3 rs307355 genotype. We assessed sweet taste threshold and preference using a series of aqueous sucrose solutions. Demographic characteristics, anthropometrics, lifestyle factors, and dietary habits were collected using a structured questionnaire. Results Sweet taste threshold positively correlated with preferred concentration in both groups (p < 0.05). A higher proportion of PwT2D with elevated preferred sweet concentrations carried one or both homozygous risk alleles (77.8%, TT/AA). When compared to healthy controls, PwT2D had higher BMI, systolic and diastolic blood pressure, and pulse rate. They also exhibited higher taste thresholds but lower preferred concentrations, though this group was significantly older, potentially confounding results. Conclusion These findings suggest taste perception and genetic variation may differ in PwT2D, highlighting the need for further research in Sub-Saharan African populations to inform personalized, cost-effective treatment strategies. However, studies with a larger sample size are required to validate our findings.